Psychometric properties of the Chalder Fatigue Scale 14 in women with postpartum depression: A cross-sectional study - Zheng, Shiyu; Nor Mazlina, Ghazali; Voon, Siok Ping; Shen, Jilin (AESS Publications, 2025)
This study aims to assess the reliability and validity of the Chalder Fatigue Scale 14 (CFS-14) in women with postpartum depression (PPD). This cross-sectional work employed purposive sampling to recruit 247 participants from three hospitals in China. This study used reliability testing, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) with the CFS-14 and the Multidimensional Fatigue Inventory (MFI-20) as the research instruments. The findings showed: (i) Reliability: The CFS-14 demonstrated good internal consistency with a Cronbach's alpha of 0.88 and a split-half reliability of 0.86. (ii) Validity: EFA identified four factors with item loadings over 0.5 except for item 14. CFA indicated an excellent model fit. Composite reliability (CR) ranged from 0.839 to 0.887 and the square root of the average variance extracted (√AVE) ranged from 0.754 to 0.893 demonstrating good construct validity. The CFS- 14 exhibited moderate to strong correlations with the MFI-20 (r = 0.456 to 0.742) supporting acceptable criterion validity. In conclusion, the instrument exhibited satisfactory reliability and validity with the CFS-14 demonstrating a solid four-factor structure instead of the original two-factor model in women with PPD after removing item 14. This enables health workers to assess fatigue and implement interventions more effectively.